The New Book of knowledge : Vol. 12 (New York : Grolier, 1983)
A twenty volume edition illustrated with maps, pictograms, and photographs in color and black and white. Entries are written on a range of reading levels and are the work of qualified specialists. Every volume is separately indexed with cross references to pertinent information found in other volumes of the set.
First published in 1912 under title: The Book of Knowledge.
Keywords: Encyclopedias and dictionaries